ANALISIS INPUT OUTPUT PENGOLAHAN TEMBAKAU DI PROVINSI JAWA TIMUR - Iswin Raka Agung Wijaya; Masyhuri Masyhuri; Irham Irham; Slamet Hartono (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2014)
This research aim at knowing tobacco and tobacco agro-industry growth inclination in Jawa Timur Regency, knowing backward and forward linkage of tobacco agro-industry sector to the other economic sectors in Jawa Timur Regency, knowing economic impact is caused by tobacco agro-industry sector base on multiplier effect of output, income, and labor in Jawa Timur Regency. This research used Input-Output Table of Domestic Transaction based on Producer Price in Jawa Timur at 2010, secondary data about land size, production, and productivity of tobacco around 2000-2011, also number of industry, labor, and tobacco ago-industry output value in Jawa Timur Regency around 2000-2011. The results of this research show that tobacco land size is declining, but number of industry, labor, and tobacco industry output value are increasing. Backward linkage for cigarette sector is low while tobacco processing sector is high. Forward linkages for both sectors are low. Cigarette sector is belonging to output and income sector with low impact, but it has high labor impact. Tobacco processing sector is belonging to output and income sector with high impact, but it has low labor impact.